Markers characterizing corneal damage during aging of rat - El-Sayyad, Hassan I. H.; El-Mansi, Ahmed A.; Guida, Mona S; Mohammed, Ezaldin AM (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Aging is a biological phenomenon that involves an increase of oxidative stress associated with gradual degradation of the structure and function of the cornea. Gender differences and subsequent deterioration of cornea is an interesting topic, especially yet few data are available concerning the impact of age, especially on the corneal. One hundred male and female Wistar albino rats ages 3, 6, 18, 24, and 30 months (n=10 equal for male and female) were used. At the time interval, cornea were investigated by light and transmission electron microscopy (TEM), immunohistochemistry of caspase 3 (casp3), glial fibrillar acidic protein(GFAP) and CD45 andÂ flow cytometry of DNA, bcl-2-like protein 4 (BAX), transforming growth factor beta (TGF-Î²) and Cd45 (lymphocyte common antigen). Light and TEM investigationÂ revealed apparent deterioration of atrophy of corneal epithelium with vesicular vacuolar degeneration, hyalinization of stromal collagen fibrils and swelling and degeneration of the endothelial lining the descemet’s membrane. There was apparent loss of keratocytes within corneal stroma. Immunohistochemistry of casp 3 and CD45 were markedly increased manifesting cell damage. GFAP showed apparent reduction of innervation of corneal stroma and endothelium layer. Flow cytometry of DNA, Bax and TGF revealed increased apoptic cell death of cornea of 30M-old rats. We concluded that aging contributed to an apparent increase of cellular damage of different corneal region associated with alterations of cell markers.